Brief Empathic Love Therapy for Depressed Adolescents Victims of Domestic Violence - Aghniacakti, Ainindita; Marfu’atun, Elya (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Adolescents who experience domestic violence are vulnerable to psychological disorders, one of which is depression. Violence perpetrated by primary attachment figures may damage an individual's self-worth, emotional balance, and hope for the future. BELT is a transpersonal therapy that emphasizes how individuals can recognize themselves more deeply, become aware of, understand, accept, and love all aspects of their being. Objective: This study aimed to examine the effectiveness of Brief Empathic Love Therapy (BELT) in reducing depressive symptoms among adolescents who are victims of domestic violence. Methods: This study employed a Small-N method using an ABA single-case design consisting of a baseline phase (A1), intervention (B), and a return to baseline (A2). BELT was delivered in two individual sessions to three adolescent females who had experienced domestic violence. Data collection tools included the Beck Depression Inventory II, Empathic Love Scale, daily depression checklist, evaluation sheet, and observation form. Data were analyzed using visual inspection. Result and Discussion: The results indicated that BELT was effective in reducing depressive symptoms and increasing empathic love in adolescent victims of domestic violence. Conclusion: The intervention also supported emotional awareness and inner acceptance, contributing to psychological recovery.